(untitled) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The train is one of the modes of transportation that has advantages compared to other modes of transportation, such as saving space, an elevated level of security, free from congestion, high carrying capacity, and environmentally friendly. One of the modes of rail transportation available at Daop 9 Jember is the Ranggajati Train which has two classes, namely executive and business. Because there are class differences, everyone has several factors in choosing the train class. Therefore, a search for the effect of variables with the selection of the Ranggajati train class will be carried. This in the future can be used as an evaluation material for PT. KAI to improve services and facilities according to the characteristics of each class. In this study, primary data collection was conducted using a Google form for passengers of the Ranggajati train in executive class and business class. The data processing and analysis method uses descriptive statistics to get an overview of the characteristics of the Ranggajati train passengers. Subsequently, calculations were done using binary logistic regression of selecting the train class. The result of the research obtained passenggers characteristics are dominated by men, 21-25 years old, work as student, travel neccesities for education, income less than 1.000.000, expenses for transportation 100.000 until 300.000, private vehicle owned motorcycle and car.